CD38 as a Therapeutic Target - Stevenson, George T (ScholarOne, 2006)
The CD38 molecule is well represented on cell surfaces in many cases of a variety of lymphoid tumors, notably multiple myeloma, AIDS-associated lymphomas, and post-transplant lymphoproliferations. As such, this molecule is a promising target for antibody therapy. After early disappointments, improved anti-CD38 antibodies of strong cytolytic potential have been described by 3 groups. First, a human IgG monoclonal anti-CD38 antibody raised in mice transgenic for human Ig has been found to induce potent complement and cellular cytotoxicities against both myeloma cell lines and fresh harvests from myeloma marrow and leukemic blood. This antibody also exhibits the singular property of inhibiting the CD38 cyclase activity. Second, a series of CD38-specific human antibodies, with high affinities and high ADCC activities against cell lines and primary cultures of myeloma, has been selected from a unique phage-display library. Finally, to enhance specificity for myeloma cells, bispecific domain antibodies targeting both CD38 and CD138 have been developed. As they lack any Fc module, these constructs rely on cytotoxicity for delivering a toxin to tumor cells. The list of candidate CD38-bearing neoplasms as targets for these antibody constructs can now be expanded to include acute promyelocytic leukemia, and possibly other myeloid leukemias, in which surface CD38 can be induced by retinoid treatment. One caveat here is that evidence has been produced to suggest that CD38 promotes pulmonary manifestations of the hazardous retinoic acid syndrome.